TEACHING READING COMPREHENSION THROUGH TASK BASED LANGUAGE TEACHING (TBLT) APPROACH TO THE SEVENTH GRADE STUDENTS AT SMP NEGERI 2 LUBUKLINGGAU - Anisah Salsabelah; ardayati; Maria Ramasari (Teaching and General Education Studies, 2026)
This research examined the effectiveness of the Task-Based Language Teaching (TBLT) approach on reading comprehension among seventh-grade students at SMP Negeri 2 Lubuklinggau for the 2024/2025 academic year. The primary challenges addressed were students' limited vocabulary and low engagement during learning activities. Using a pre-experimental method, the study focused on class VII.11 (38 students) selected through cluster random sampling. Data were collected via multiple-choice tests and analysed using normality testing and a matched t-test. The results showed significant improvement: the average score rose from 61.57 in the pre-test to 75.00 in the post-test. Statistically, the t-obtained value of 7.33 exceeded the t-table value of 1.687, proving TBLT's effectiveness. This approach enhanced comprehension by fostering active participation and contextual learning. The study recommends implementing TBLT across different grade levels or other language skills to further explore its educational impact and broaden the evidence of its success.